2019
DOI: 10.1007/s00791-018-00307-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of a phase field model for polycrystallization processes in binary mixtures

Abstract: We consider the numerical solution of a phase field model for polycrystallization in the solidification of binary mixtures in a domain Ω ⊂ R 2 . The model is based on a free energy in terms of three order parameters: the local orientation Θ of the crystals, the local crystallinity φ, and the concentration c of one of the components of the binary mixture. The equations of motion are given by an initial-boundary value problem for a coupled system of partial differential equations consisting of a regularized seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In fact, a uniform choice τ m = T/M only works, if M is chosen sufficiently large which would require an unnecessary huge amount of time steps. An appropriate way to overcome this difficulty is to consider (5.2a), (5.2b) as parameter dependent nonlinear systems with the time as a parameter and to apply a predictor-corrector continuation strategy with an adaptive choice of the time steps (cf., e.g., [5,12,13,14]). Given the pair (Θ m−1 , Φ m−1 ), the time step size τ m−1,0 = τ m−1 , and setting k = 0, where k is a counter for the predictor-corrector steps, the predictor step for (5.2a) consists of constant continuation leading to the initial guesses…”
Section: Discretization In Space and Numerical Solution Of The Fully ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a uniform choice τ m = T/M only works, if M is chosen sufficiently large which would require an unnecessary huge amount of time steps. An appropriate way to overcome this difficulty is to consider (5.2a), (5.2b) as parameter dependent nonlinear systems with the time as a parameter and to apply a predictor-corrector continuation strategy with an adaptive choice of the time steps (cf., e.g., [5,12,13,14]). Given the pair (Θ m−1 , Φ m−1 ), the time step size τ m−1,0 = τ m−1 , and setting k = 0, where k is a counter for the predictor-corrector steps, the predictor step for (5.2a) consists of constant continuation leading to the initial guesses…”
Section: Discretization In Space and Numerical Solution Of The Fully ...mentioning
confidence: 99%
“…In [8], the authors suggested a phase field model featuring an orientational free energy density f ori in the phase field variables (local degree of crystallinity ϕ and orientation angle Θ) which takes care of misorientation. As a function of Θ, the orientational free energy density is related to the total variation of Θ. Consequently, from a mathematical point of view one has to consider Θ in the Banach space BV of functions of bounded variation as has been done in [13] for the two-field Kobayashi-Warren-Carter model [15] and in [14] for a three-field phase field model for polycrystalline growth in binary mixtures. As far as the minimization of functionals in terms of the total variation is concerned, there is a fundamental result stated in [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation